PROSES HIDROLISA PATI TALAS SENTE (Alocasia macrorrhiza) MENJADI GLUKOSA : STUDI KINETIKA REAKSI - Astrinia Aurora Dinarsari; Alfiana Adhitasari (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Starch hydrolysis process is the method used in the conversion of starch to glucose from starch material such as Giant Taro (Alocasia Macrorrhiza) using acid catalyst. In this study starch hydrolysis of Giant Taro using hydrochloric acid catalyst is divided into three stages of continuous process that aims to obtain a good pH and temperature on starch hydrolysis process of Giant Taro and studying the kinetics process of starch hydrolysis of Giant Taro into glucose. The experiments were performed using a fixed variable, namely particle size of starch 20 mesh, the ratio of raw material to water is 1:30 (g starch / ml of water), stirring speed 200 rpm and reaction time 60 minutes.There are two random variables i.e. pH 2, 3, 4, 5 and temperature of reaction 500C, 600C, 700C, 800C, 900C. Results of hydrolysis were analyzed using the DNS method to determine glucose levels. The result showed good pH at pH 4 and temperature at 900C, the reaction rate constant k is 9,139x10-4/min and reaction rate equation of hydrolysis is CA = 0,03740164. e- 0,0009139. t.